Distribution channel problem faced by Faiza Marketing Sdn Bhd / Sharifah Badariah Syed Ali - Syed Ali, Sharifah Badariah (2009)
This study was carried out at Faiza Marketing Sdn. Bhd (FMSB). The main purpose of this study is to find out the distribution channel problem faced in the company. This study will give more useful information to FMSB in order for them to overcome the problem in their distribution strategy and delivering their product. After an observation in the company during the practical training and interview session with the company staff, researcher had found the best way for the company to solve their distribution problem. The findings of the study will hopefully be guideline for FMSB to recognize their distribution problem, to improve their distribution strategy and deliver their product by using type of intermediaries that will give more benefit to the company.